Poemas amazônicos em sala de aula: um incentivo à valorização da cultura, leitura e produção de textos no ensino fundamental - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The present work has as main title Amazon Poems in the classroom: an incentive to the valorization of the culture, reading and production of texts in the elementary school, and brings as title of the Amazon intervention proposal in verses: Reading of poems in class, as an incentive to the valorization of the literary production of Amazonian poets. The methodological proposal resulted in a pedagogical material as a suggestion to be used by elementary school teachers. However, as a test, this proposal was applied in a 6th grade class of the Municipal School of Elementary Education of São Francisco, municipality of Óbidos-Pa. In order to achieve the desired results, this dissertation was based on bibliographical research, qualitative and participant. In this sense, the main objective of this study was to study the poems of Amazonian authors, identifying the possible obstacles to the absence of these texts in primary education and, using this method, using methodologies for reading and writing and oral production. the exercise of these readings in the daily life of the elementary school student. In order to reach this objective, this work discusses, in four chapters, themes that will contribute to the development of reading, oral and written production of students in elementary school, as well as activities that will favor the awakening of the valorization of literary productions Amazon region. Thus, the results show the need for students to know the works of authors of this region, which was noticed during the discussions in the classroom. And everything was confirmed from the evaluation, at which point the students, through their lines, demonstrated their satisfaction in having read poets of the Amazon region. The main theorists who supported this dissertation were: Candido, Britto, Moisés.
Keywords: Leitura; Literatura; Literatura Brasileira; Expressão Amazônica; Poemas Amazônicos; Produção Oral e Escrita; CNPQ::CIÊNCIAS HUMANAS